The effect of Ramadan intermittent fasting on anthropometric, hormonal, metabolic, inflammatory, and oxidative stress markers in pre-and post-menopausal women: a prospective cohort of Saudi women - Al Zunaidy, Nada A.; Al-Khalifa, Abdulrahman S.; Alhussain, Maha H.; Althwab, Sami A.; Mohammed, Mohammed A.; Faris, MoezAlIslam E. (Frontiers in Nutrition, 2024)
The menopausal transition significantly affects cardiometabolic health, primarily due to changes in reproductive hormones, particularly decreased estrogen levels and relative androgen excess. Adult Muslim women, both pre-and post-menopausal, are mandated to observe Ramadan intermittent fasting (RIF) every year. Therefore, the current study was designed to investigate RIF's effects on premenopausal (PRE-M) and postmenopausal (POST-M) healthy women's cardiometabolic health markers. The study further evaluated the relationship between tested markers and participants' basic variables, such as BMI and body fatness. Due to differences in physiological and metabolic biomarkers between groups, RIF is likely to impact PRE-M and POST-M women differently. Methods: The study included 62 healthy women (31 PRE-M, aged 21-42 years, and 31 POST-M, aged 43-68 years) who observed RIF. Anthropometrics, sex hormones, lipid profile, pro-inflammatory (TNF-α) and antiinflammatory (IL-10) cytokines, the oxidative stress markers malondialdehyde (MDA), total antioxidant capacity (TAC), superoxide dismutase (SOD), glutathione peroxidase (GPx) and aging biomarker insulinlike growth factor-1 (IGF-1); all were tested one week before and at the fourth week of Ramadan. Results: Body weight, BMI, waist circumference, body fat percent (BFP), fat mass, fat mass index, triglycerides, and diastolic blood pressure significantly (p<0.05) decreased at the end of Ramadan in both groups in comparison to the pre-fasting period. Contrarily, HDL, SOD, GPx, and IL-10 significantly (p<0.05) increased in both groups. Estrogen levels significantly (p<0.05) decreased in PRE-M women, whereas significantly (p<0.05) increased in POST-M women. The progesterone levels, TAC, MDA, and IGF-1 remained unchanged in both groups. TNF-α significantly decreased in both groups, but the magnitude of reduction was higher in PRE-M women. Sex hormones and some metabolic biomarkers, especially in POST-M women, variably exhibited positive or negative relationships to BMI and BFP. RIF may influence the levels of estrogen, TNF-α, and IL-10 through improvements in metabolic health, reductions in body fat, activation of autophagy, modulation of immune responses, and changes in hormonal regulation.The RIF was generally associated with improved anthropometric, metabolic, inflammatory, and oxidative stress markers in both PRE-M and POST-M healthy women. Adhering to healthy dietary and lifestyle guidelines by pre-and post-menopausal women during Ramadan may foster the health benefits gained.